Tumour Resection Volumes and Facial Nerve Outcomes for Vestibular Schwannomas - Virk, Jagdeep Singh (Springer India, 2014)
The objective of this study is to correlate tumour volume relationship with surgical outcomes in subtotal resections and accepted nomenclature through a retrospective study at Charing Cross Hospital, London, a tertiary referral centre. The participants were 16 patients with vestibular schwannoma managed with subtotal resection between 2002 and 2011. The main outcome measures were surgical technique; tumour volume; recurrence and post-operative facial nerve function. Mean pre-operative and post-operative volumes for all patients were 14.7 and 3.7 cm(3) respectively. Tumour volumes do not correlate with diameter (p < 0.05). Mean reduction in volume of these subtotal resections was 75 %. Long term facial nerve outcome was good in the majority of patients: House–Brackmann Grade I/II in 12 (75 %), Grade III/IV in 2 (12.5 %) and Grade V/VI in 2 patients (12.5 %). Notably, two patients with Grade I/II House–Brackmann grading later developed Grade V/VI palsy following adjunctive radiotherapy. Seven of the 16 subtotal resections had subsequent radiotherapy or microsurgery. Mean follow up was 26.5 months. In conclusion, subtotal resections lead to good facial nerve outcomes but may require further treatments. Radiation treatment can worsen facial nerve function. There is no standardised use of tumour volumes or accepted guidelines for resection terminology. We propose the use of tumour volumes to define this further.